Preparation method and application of Au cluster modified PtCu nano dendritic catalyst

By introducing Au clusters on PtCu nanobranches, the problem of poor stability of Pt/C catalysts in methanol oxidation reaction is solved, and a high activity and high stability catalyst is achieved, which simplifies the preparation process and reduces costs and promotes fuel Battery industrialization.

CN119315042APending Publication Date: 2025-01-14HANGZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310872500.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing Pt/C catalysts have poor stability, low activity and are expensive in methanol oxidation reaction, making it difficult to achieve commercial application.

Method used

Au clusters were introduced by a one-step method through spontaneous current substitution reaction on PtCu nanobranches to prepare Au cluster-modified PtCu nanobranch catalysts to improve their methanol oxidation activity and stability.

Benefits of technology

A catalyst with high activity and high stability is achieved, the preparation process is simplified, the cost is reduced, the demand for methanol fuel cell anode catalyst is met, and the fuel cell industrialization is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315042A_ABST
    Figure CN119315042A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysts, and discloses a preparation method and application of an Au cluster modified PtCu nano-dendritic catalyst. The preparation method comprises the following steps: (a) mixing, stirring and heating a platinum source compound and alkylamine, adding a copper source compound and alkylamine, and continuously heating and stirring for reaction to prepare PtCu nano dendritic particles; and (b) dispersing the PtCu nano dendritic particles in an organic solvent, adding alkylamine, adding a gold source compound solution, stirring for reaction, and centrifugally washing to obtain the catalyst. The Au cluster modified PtCu nano dendritic catalyst is successfully synthesized by replacing an Au precursor with a Cu element in an in-situ galvanic couple manner on the surfaces of PtCu nano dendritic particles, and the method is simple in synthesis process, mild in synthesis condition and suitable for large-scale preparation. The Au cluster modified PtCu nano dendritic catalyst disclosed by the invention has relatively high methanol electrooxidation activity and methanol electrooxidation stability at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a preparation method and application of a PtCu nano-dendritic catalyst modified by Au clusters. Background Art

[0002] With the continuous development of society and economy, traditional fossil energy has become scarce. The development and utilization of new energy technologies is an important way to solve the above problems. Among many new energy technologies, fuel cells have attracted widespread attention due to their advantages such as high energy density. Among them, direct methanol fuel cells have the characteristics of simple operation and stable operation, and have attracted the attention of more and more researchers. As a portable power source, it is widely used in electric vehicles and other fields. The development and utilization of direct methanol fuel cells is of great significance.

[0003] The key to the reaction in direct methanol fuel cells is to select highly active and highly selective catalysts to improve the conversion rate of the reactants. At present, the most commonly used catalyst in methanol oxidation reactions is Pt / C catalyst, but Pt is expensive, has poor stability, and low activity, and it is still a certain distance away from true commercialization. For example, a paper published in the top international journal ACS Appl. Energy Mater. (Degradation mechanisms of supported Ptnanocatalysts in proton exchange membrane fuel cells: an operando study through liquid cell transmission electron microscopy, ACS Appl. Energy Mater. 2022, 3, 2360–2371) mentioned that the activity loss of Pt-based catalysts after long-term operation of methanol oxidation is a very important issue, which is mainly caused by the Ostwald ripening of transition metal Pt under high potential and acidic conditions. Therefore, how to improve the stability of Pt while maintaining its high catalytic activity and improving its stability has become the focus of extensive research. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation method and application of a PtCu nano-dendritic catalyst modified by Au clusters. The present invention first synthesizes a PtCu nano-dendritic catalyst with high activity on the basis of a Pt-based catalyst, and then further introduces an Au cluster to obtain a PtCu nano-dendritic catalyst modified by Au clusters with high activity and high stability. The present invention can overcome the problems in the prior art that when Pt / C catalysts are used for methanol oxidation reactions, the Pt-based catalysts have poor stability, low activity, high prices, and are difficult to achieve true commercial applications.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing a PtCu nanodendritic catalyst modified by Au clusters, comprising the following steps: (a) A platinum source compound and an alkylamine are stirred and mixed, and heated under an inert atmosphere. A mixed solution of a copper source compound and an alkylamine is added, and the mixture is heated and stirred to react, thereby obtaining PtCu nano-dendritic particles.

[0006] (b) dispersing the PtCu nano-dendritic particles in an organic solvent, adding an alkylamine, adding a gold source compound solution dispersed in the organic solvent under stirring conditions, stirring for reaction, and washing the obtained product by centrifugation with an organic solvent to obtain a PtCu nano-dendritic catalyst modified with Au clusters.

[0007] Previous studies have shown that dealloyed PtCu exhibits very good activity. Therefore, PtCu alloy may be a suitable raw material for surface modification. The present invention adopts a one-step method, that is, starting from PtCu nano-dendritic dendrites, using the surface Cu element and Au 3+ The spontaneous current substitution reaction directly modifies Au clusters on PtCu nano-densities, and the catalyst has high methanol oxidation activity and stability. Among them, PtCu nano-densities ensure high methanol oxidation activity, and the introduction of Au clusters ensures the durability and stability of PtCu nano-densities.

[0008] Preferably, in step (a), the platinum source compound is selected from chloroplatinic acid hexahydrate, potassium chloroplatinate and sodium chloroplatinate; the copper source compound is selected from copper acetylacetonate, copper chloride and copper sulfate; and the alkylamine is selected from hexadecylamine, octadecylamine and oleylamine.

[0009] Preferably, in step (a), the usage ratio of the platinum source compound, the copper source compound and the alkylamine is (30.0-50.0 mg): (30.0-50.0 mg): (0.5-5.0 mL).

[0010] Preferably, in step (a), the temperature is 15-25°C·min −1 The mixture was heated with stirring at a speed of 100 ° C., and when the mixture was heated to 140-160 ° C., a mixed solution of the copper source compound and the alkylamine was added; the mixture was heated to 190-210 ° C. and then stopped heating, and the reaction lasted for 15-120 min; after the reaction, the mixture was cooled to 90-110 ° C., toluene was added, and the mixture was centrifuged for 1-3 min.

[0011] Preferably, in step (b), the gold source compound is chloroauric acid; and the organic solvent is selected from toluene, chloroform and n-hexane.

[0012] Preferably, in step (b), the ratio of the PtCu nano-dendritic particles to the organic solvent is (0.03-0.86 mmol): (2.0-17.0 mL); the ratio of the PtCu nano-dendritic particles to the alkylamine is (3.0-15.0 mL): (0.20-5.00 mL); and the ratio of the gold source compound to the organic solvent is (0.015-0.955 mmol): (0.25-5.50 mL); the ratio of the PtCu nano-dendritic particles to the gold source compound is (0.05-1 mmol): (0-0.05 mmol).

[0013] Preferably, in step (b), the gold source compound solution is added within 10 minutes, and the stirring reaction time is 20-40 minutes.

[0014] In a second aspect, the present invention provides an application of the Au cluster-modified PtCu nanodendrite catalyst obtained by the above-mentioned preparation method in the preparation of an electrochemical reaction working electrode: the Au cluster-modified PtCu nanodendrite catalyst is dispersed in a mixed solution consisting of water, isopropanol and Nafion; the obtained dispersion is dropped onto the electrode surface and dried to prepare a working electrode.

[0015] Preferably, the volume ratio of water, isopropanol and Nafion is (3-5):1:(0.02-0.03).

[0016] Preferably, the concentration of the Au cluster-modified PtCu nanodendritic catalyst in the mixed solution is 2.0-85.0 mg· mL −1 .

[0017] Compared with the prior art, the beneficial effects of the present invention are: (1) Compared with commercial Pt / C catalysts, the Au cluster-modified PtCu nanodendritic catalysts of the present invention have both higher methanol oxidation activity and higher methanol oxidation stability.

[0018] (2) Compared with the prior art which deposits Au clusters on the Pt surface by a complex method of underpotential deposition, the present invention adopts a one-step in-situ current substitution reaction on the PtCu surface to modify Au clusters, which is simple to operate and has high synthesis efficiency.

[0019] (3) The catalyst prepared and the synthesis process of the present invention can meet the demand for anode catalysts of methanol fuel cells and are helpful in promoting the industrialization of fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a SEM image of the catalyst prepared in Example 1; Figure 2is a SEM image of the catalyst prepared in Comparative Example 1; Figure 3 is a size distribution diagram of the catalyst prepared in Example 1; Figure 4 is the HRTEM image of the catalyst prepared in Example 1; Figure 5 is the XRD diagram of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2; Figure 6 is a selected electron diffraction pattern of the catalyst prepared in Example 1; Figure 7 TEM image (a) and EDS spectrum (be) of the stability test of Example 1; Figure 8 The stability of comparative example 2, comparative example 1 and example 1 in methanol oxidation reaction; CV curves of methanol oxidation reaction in 0.5M H2SO4+0.5MCH3OH before and after 5000 cycles of comparative example 2 (a), comparative example 1 (b) and example 1 (c); (d) comparison of methanol oxidation reaction activity of three catalysts before and after cycles; Fig. 9 CV curves of the first cycle, second cycle and stable cycle of Comparative Example 2 (a), Comparative Example 1 (b) and Example 1 (c) in 0.5M H2SO4 solution; (d) CO stripping curves of the three catalysts in 0.5M H2SO4 solution; (e) comparison of the electrochemical surface areas (ECSA) of the three catalysts measured by hydrogen desorption (left) and CO desorption (right). DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the embodiments.

[0022] Overall embodiment A method for preparing a PtCu nano-dendritic catalyst modified by Au clusters comprises the following steps: (a) The platinum source compound and the alkylamine are stirred and mixed, and heated under an inert atmosphere at 15-25°C·min −1 The mixture was heated with stirring at a speed of 1000 to 2000 °C, and a mixed solution of the copper source compound and the alkylamine was added when the mixture was heated to 140-160 °C. The mixture was heated to 190-210 °C and then stopped, and the mixture was reacted for 15-120 min. After the reaction, the mixture was cooled to 90-110 °C, toluene was added, and the mixture was centrifuged for 1-3 min to obtain PtCu nano-dendritic particles.

[0023] Preferably, the platinum source compound is selected from chloroplatinic acid hexahydrate, potassium chloroplatinate and sodium chloroplatinate; the copper source compound is selected from copper acetylacetonate, copper chloride and copper sulfate; the alkylamine is selected from hexadecylamine, octadecylamine and oleylamine. The amount ratio of the platinum source compound, the copper source compound and the alkylamine is (30.0-50.0 mg): (30.0-50.0 mg): (0.5-5.0 mL).

[0024] (b) The PtCu nano-dendritic particles are dispersed in an organic solvent, an alkylamine is added, and a gold source compound solution dispersed in the organic solvent is added within 10 minutes under stirring conditions, and the reaction is stirred for 20-40 minutes. The obtained product is washed by centrifugation with an organic solvent to obtain a PtCu nano-dendritic catalyst modified with Au clusters.

[0025] Preferably, the gold source compound is chloroauric acid; the organic solvent is selected from toluene, chloroform and n-hexane. The ratio of the PtCu nano-dendritic particles to the organic solvent is (0.03-0.86 mmol): (2.0-17.0 mL); the ratio of the PtCu nano-dendritic particles to the alkylamine is (3.0-15.0 mL): (0.20-5.00 mL); and the ratio of the gold source compound to the organic solvent is (0.015-0.955 mmol): (0.25-5.50 mL); the ratio of the PtCu nano-dendritic particles to the gold source compound is (0.05-1 mmol): (0-0.05 mmol).

[0026] A method for preparing an electrochemical reaction working electrode comprises: dispersing a PtCu nano-dendritic catalyst modified by Au clusters in a mixed solution of water, isopropanol and Nafion; dripping the obtained dispersion onto the electrode surface, and drying to prepare the working electrode.

[0027] Preferably, the volume ratio of water, isopropanol and Nafion is (3-5):1:(0.02-0.03). The concentration of the Au cluster-modified PtCu nanodendritic catalyst in the mixed solution is 2.0-85.0 mg· mL −1 .

[0028] Example 1 (1) Add hexadecylamine (17 mmol, 4.6 g) and chloroplatinic acid hexahydrate (0.05 mmol, 25.9 mg) into a 50 mL three-necked flask, and introduce nitrogen as a protective gas into the reaction system. Turn on the magnetic stirrer and heat at 20 °C min −1When the temperature rises to 150°C, add copper acetylacetonate (0.1 mmol, 39.3 mg) and 1.0 mL of oleylamine mixed liquid (pre-heated and dissolved) into the three-necked flask. When the temperature rises to 200°C, stop heating and react for 40 minutes. After the reaction is completed, cool to 100°C, add a certain amount of toluene, and centrifuge for 2 minutes (5000 rpm) to obtain PtCu nano-dendritic particles.

[0029] (2) Add 5 ml of approximately 0.05 mmol of PtCu nanodendritic particles dispersed in toluene to a small glass bottle, then add 0.50 mL of oleylamine while stirring, and then slowly add the freshly prepared chloroauric acid solution. Chloroauric acid solution refers to a mixed solution formed by dispersing 0.05 mmol of chloroauric acid in 1.0 mL of chloroform. The chloroauric acid solution is added within 10 minutes and the reaction is stopped after stirring for another 30 minutes. The Au cluster-modified PtCu nanodendritic catalyst is collected by centrifugation and washed several times to remove the oleylamine ligand and unreacted chloroauric acid.

[0030] The Au cluster-modified PtCu nanodendritic catalyst prepared above was made into a working electrode by the following method: The catalyst was dispersed in 1 mL of a mixed solution consisting of water, isopropanol, and Nafion (volume ratio 4:1: 0.025). The catalyst concentration was controlled at 4 mg mL −1 About 3 μL of the obtained solution was dropped on the surface of the glassy carbon electrode and then dried at room temperature to obtain the Au cluster-modified PtCu nanodendritic catalyst to make a working electrode.

[0031] Comparative Example 1 The preparation method of PtCu nano-dendritic catalyst (PtCu3) is the same as that in Example 1 (1).

[0032] Comparative Example 2 The preparation method of Pt / C nanocatalyst comprises the following steps: 30 mg XC-72 carbon black and 20 mg NaOH were added to the mortar and ground thoroughly. Sufficient water was extracted into the mortar to wash off the unmodified NaOH. Subsequently, 0.1 mmol hexahydrate chloroplatinic acid and 0.5 mL NH4OH were added to the mortar and ground for 30 minutes. Subsequently, 15 mg NaBH4 was added and ground continuously for 30 minutes to reduce the Pt precursor to small Pt nanoparticles.

[0033] The obtained powder was thoroughly washed with deionized water to remove residual impurities. The Pt-SNPs / C catalyst was collected by centrifugation. After washing with ethanol several times, the Pt-SNPs / C catalyst was obtained by drying at 60 °C overnight. The importance of NaOH and NH4OH in the synthesis was clarified by control experiments, during which no NaOH or NH4OH was added during the entire synthesis. The other procedures were the same as described above.

[0034] Performance Testing The catalysts prepared in Example 1 and Comparative Example 1 were subjected to SEM analysis. Figure 1 , 2 As shown. Figure 2 It can be seen that the PtCu nano-dendritic catalyst prepared by the method of the present invention in Comparative Example 1 is uniformly dispersed, with an average size of 73±9 nm and a highly branched structure. Figure 1 It can be seen that the Au cluster-modified PtCu nano-dendrite catalyst was prepared in Example 1, and its morphology and size did not change significantly compared with the PtCu nano-dendrite catalyst.

[0035] The catalyst prepared in Example 1 was analyzed for size distribution. Figure 3 As shown, from Figure 3 It can be seen that the catalyst particles prepared by the present invention are nanometer-level, with an average size of 73±9nm.

[0036] The catalyst prepared in Example 1 was subjected to HRTEM analysis, and the results were as follows: Figure 4 As shown, from Figure 4 It can be seen that in the catalyst particles prepared by the present invention, Au exists in the form of clusters or below clusters, and the PtCu-Au surface has twin boundaries, which can greatly improve its catalytic activity for specific reactions.

[0037] The catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to XRD analysis. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the morphology, size and structure of Cu and Au do not change before and after treatment, indicating that the modification mainly occurs on the surface.

[0038] The catalyst prepared in Example 1 was subjected to electron diffraction analysis, and the results were as follows: Figure 6 As shown, from Figure 6 It can be seen that the catalyst particles prepared by the present invention.

[0039] The catalyst prepared in Example 1 was subjected to 5000 cycles of testing, and the catalyst after the reaction was subjected to TEM and EDS characterization tests. Figure 7 As shown, from Figure 7 It can be seen that the Au cluster-modified PtCu nanodendritic catalyst prepared by the present invention has more holes observed after the GRR process due to the diffusion of copper in the GRR process caused by the Kirkendall effect. The morphology, size and structure before and after the treatment do not change, and the cycle performance is excellent.

[0040] The catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested for methanol oxidation reaction specific activity before and after 5000 cycles. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that although the PtCu-Au catalyst loses 20% of its ECSA compared to the PtCu nanoparticles, its methanol oxidation activity is still much higher than that of the Pt / C catalyst. The initial methanol oxidation reaction mass activities of Pt / C, PtCu nanodendrites, and PtCu-Au are 0.37 mA mg -1 、1.44mA mg -2 and 1.20mA mg -3 ( Figure 8 ac). After 5000 cycles, the mass activity of methanol oxidation reaction decreased to 0.20 mA mg -1 、0.81mA mg -1 and 1.10mA mg -l ( Figure 8 ac). The activity loss of PtCu-Au (7%) is much smaller than that of Pt / C (46%) and PtCu nanodendrites (45%) ( Figure 8 d). The difference in the activities of the three catalysts indicates that the superior stability of PtCu-Au comes from the negligible loss of Pt and Cu due to the stabilizing effect of Au.

[0041] The surface properties of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were detected by continuous cyclic voltammetry (CV), and the first cycle, second cycle and stable cycle of the catalysts were recorded and compared. For the nano-dendrites in Comparative Example 1, it was directly observed that the oxidation peak of Cu gradually decreased with the cycle ( Fig. 9 b), indicating that Cu gradually dissolves. The disappearance of the copper oxidation peak indicates the formation of a PtCu / Pt dealloyed core-shell structure. In contrast, for Example 1, the oxidation peak of Cu is much smaller than that of PtCu nanodendrites ( Fig. 9 c), indicating that most of the surface Cu was replaced by Au galvanic couples. The remaining surface Cu can be removed by CV activation. The hydrogen zone peak area of ​​PtCu nanodendrites and PtCu-Au gradually increased with cycling, indicating that the electrochemical surface area (ECSA) increased during the removal of surface Cu. Comparative Example 2 did not show significant changes during cycling ( Fig. 9a). CO stripping measurements were used to further estimate the surface properties of the three catalysts after CV activation and to evaluate the ECSA. The different peak potentials of CO stripping of the three catalysts indicate that there is a strong electronic interaction between Pt, Cu, and Au ( Fig. 9 d). The ECSAs of the three catalysts evaluated from hydrogen desorption or CO stripping are basically consistent ( Fig. 9 e). The ECSA of PtCu-Au is about 20% smaller than that of PtCu nanodendrites, indicating that about 20% of the surface of PtCu-Au is covered by Au.

[0042] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0043] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a PtCu nanodendritic catalyst modified by Au clusters, characterized in that The following steps are involved: (a) stirring and mixing a platinum source compound and an alkylamine, stirring and heating under an inert atmosphere, adding a mixed solution of a copper source compound and an alkylamine, and continuing to heat and stir to react, thereby obtaining PtCu nano-dendritic particles; (b) dispersing the PtCu nano-dendritic particles in an organic solvent, adding an alkylamine, adding a gold source compound solution dispersed in the organic solvent under stirring conditions, stirring for reaction, and washing the obtained product by centrifugation with an organic solvent to obtain a PtCu nano-dendritic catalyst modified with Au clusters.

2. The preparation method according to claim 1, characterized in that: In step (a), The platinum source compound is selected from chloroplatinic acid hexahydrate, potassium chloroplatinate and sodium chloroplatinate; and / or The copper source compound is selected from copper acetylacetonate, copper chloride and copper sulfate; and / or The alkylamine is selected from hexadecylamine, octadecylamine and oleylamine.

3. The preparation method according to claim 1 or 2, characterized in that: In step (a), The usage ratio of the platinum source compound, the copper source compound and the alkylamine is (30.0-50.0 mg): (30.0-50.0 mg): (0.5-5.0 mL).

4. The preparation method according to claim 1 or 2, characterized in that: In step (a), 15-25°C·min −1 The mixture was heated with stirring at a speed of 100 ° C., and when the mixture was heated to 140-160 ° C., a mixed solution of the copper source compound and the alkylamine was added; the mixture was heated to 190-210 ° C. and then stopped heating, and the reaction lasted for 15-120 min; after the reaction, the mixture was cooled to 90-110 ° C., toluene was added, and the mixture was centrifuged for 1-3 min.

5. The preparation method according to claim 1, characterized in that: In step (b), The gold source compound is chloroauric acid; and / or The organic solvent is selected from toluene, chloroform and n-hexane.

6. The preparation method according to claim 1 or 5, characterized in that: In step (b), The ratio of the PtCu nano-dendritic particles to the organic solvent is (0.03-0.86 mmol): (2.0-17.0 mL); and / or The ratio of the PtCu nano-densities to the alkylamine is (3.0-15.0 mL): (0.20-5.00 mL); and / or The ratio of the gold source compound to the organic solvent is (0.015-0.955 mmol): (0.25-5.50 mL); and / or The ratio of the PtCu nano-dendritic particles to the gold source compound is (0.05-1 mmol): (0-0.05 mmol).

7. The preparation method according to claim 1 or 5, characterized in that: In step (b), The gold source compound solution is added within 10 minutes, and the stirring reaction time is 20-40 minutes.

8. Use of the Au cluster-modified PtCu nanodendritic catalyst obtained by the preparation method according to any one of claims 1 to 7 in preparing an electrochemical reaction working electrode, characterized in that: The Au cluster-modified PtCu nano-dendritic catalyst is dispersed in a mixed solution consisting of water, isopropanol and Nafion; the obtained dispersion is dropped onto the electrode surface and dried to prepare a working electrode.

9. The use according to claim 9, characterized in that: The volume ratio of water, isopropanol and Nafion is (3-5):1:(0.02-0.03).

10. The use according to claim 8 or 9, characterized in that: The concentration of the Au cluster-modified PtCu nanodendritic catalyst in the mixed solution is 2.0-85.0 mg· mL −1 .